﻿Searching for novel antagonists of adenosine A1 receptors among azolo[1,5-a]pyrimidine nitro derivatives - Dmitry S. Yakovlev; Pavel M. Vassiliev; Yana V. Agatsarskaya; Anastasia A. Brigadirova; Kira T. Sultanova; Maria O. Skripka; Alexander A. Spasov; Konstantin V. Savateev; Vladimir L. Rusinov; Dmitriy V. Maltsev (Belgorod National Research University, 2022)
Introduction: Ligands of adenosine A1Rs are potential candidates for the development of drugs for the treatment of paroxysmal supraventricular tachycardia, angina pectoris, hypertriglyceridemia, type 2 diabetes mellitus, neuropathic pain, and heart failure. At the same time, there is a deficiency of drugs that can regulate the functions of A1 receptors. A number of A1-antagonists are at the various stages of clinical trials; other drugs are not very selective or are characterized by an insufficient breadth of their therapeutic action. Therefore, the search for new medicinal compounds for the prevention and treatment of A1-depended diseases among nitro derivatives of tetrazolo[1,5-a]pyrimidine and ﻿1,2,4-triazolo[1,5-a]pyrimidine﻿ is of scientific interest. Materials and methods: The search for active compounds was carried out by in silico and in vitro methods. At the first stage, a computer forecast of A1-antagonistic activity was carried out using the Microcosm BioS software. At the second stage, the prediction results were verified in vitro in a model of isolated mouse atria. Results and discussion: Based on the results of the prediction by the method of maximum similarity to standards, the most active compounds III, VIII, and XVII were selected. After testing the prediction results by the isolated atria method, the compound VIII was characterized by A1-blocking effect in vitro at a concentration of 10 μmol/L. Conclusion: The most promising compound with A1-blocking effect in vitro was identified; it is a derivative of tetrazolo[1,5-a]pyrimidine under the code of VIII. It is of interest for us for further in-depth study of its pharmacological properties.